PATIENT IDENTIFICATION RELATED TO PATIENT SATISFACTION - Masrurin Masrurin; Sih Ageng Lumadi; Lilla Maria (Jurnal Kesehatan Mesencephalon, 2022)
Patient identification is an effort to find out the patient's identity through the ID number (KTP/ SIM/Student Card/Student Card) and date of birth to facilitate the provision of services to patients. The purpose of the study was to determine the relationship between the correct implementation of patient identification and patient satisfaction in Room 27. The research design used a correlative study with a cross sectional approach. The population of this study were all patients in room 27 who met the inclusion criteria and exclusion criteria with a total sample of 123 respondents. The results showed that most of the patients identified well and expressed satisfaction 101 respondents (82.11%), patients who were identified as good and stated dissatisfied 10 respondents (8.1%) and patients who were identified quite well and were not satisfied 12 respondents (9.75%). The statistical test used the chi-square test (x²) at a significance level of 95% (α = 0.05). The results obtained p-value = 0.000 with a level of significance